THE EFFECT OF SERVICE QUALITY ON COMMUNITY SATISFACTION AT THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION (DISPENDUKCAPIL) BANYUWANGI CITY - Saifudin, Saifudin; Ximenes, Mateus; Widagdo, Suwignyo; H P, Agustin (Institut Teknologi dan Sains Mandala, 2021)
Public service is one manifestation of the function of the state apparatus as a public servant, public service for the welfare of the community or citizens. Professional service means service that is characterized by public accountability and responsibility from public service providers. One of the functions that must be carried out by the government is the function of public services or the function of community services. To see it all can be packaged in the quality of service (real, reliability, responsiveness, assurance, empathy). The purpose of this study is to test and analyze the effect of the dimensions of service quality (real, reliability, responsiveness, assurance, empathy) simultaneously and partially on community satisfaction simultaneously at the Population and Civil Registration Service (DISPENDUKCAPIL) Banyuwangi City and see the most dominant variables. in service quality. The sample in this study was 138 respondents who used the purposive sampling technique. Data analysis used multiple regression tests, hypothesis testing, and coefficient of determination (R2). Based on the research, it is explained that all service quality variables have a simultaneous effect on people's satisfaction while partially three variables influence them (tangibles, reliability, and responsiveness) and two other variables. (certainty and empathy) do not affect employee satisfaction. From the fifth variable, it turns out that tangible variables (Physical Evidence) have a dominant influence on people's satisfaction.. Keyword: tangibles, realibility, responsivisness, assurance, empathy, and satisfaction